Optimizing antimicrobial drug dosing in critically ill patients - Póvoa, Pedro (2021)
Funding Information: Conflicts of Interest: P.P. has received lecture fees and advisory board from MSD, Gilead, Pfizer; L.C. and P.M. declared no conflicts of interest related to the underlying topics; J.G.P. received unre‐ stricted research grants from Merck Sharp and Dohme; received lecture and advisory board fees from Merck Sharp and Dohme, Angelini Pharmaceuticals; lecture fees from Pfizer Pharmaceuticals, Atral Pharmaceuticals, Biomerieux. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland. Copyright: Copyright 2021 Elsevier B.V., All rights reserved.